Pengaruh Kompensasi dan Kompetensi terhadap Kinerja Karyawan Outsourcing pada PT Indonesia Power UPJP Kamojang Kabupaten Bandung - Tatang Mulyana (Jurnal Wacana Ekonomi, 2017)
PT. Indonesia Power UPJP Kamojang is a state-owned company engaged in electric power generation and Power Plant Operation and Maintenance Services, PT. Indonesia Power plays an important role in electricity and geothermal in Indonesia. To have a good performance, PT. Indonesia Power UPJP Kamojang must provide appropriate compensation to motivate work enthusiasm in achieving optimal work performance and superior competencies to achieve organizational targets. The method used in this research is descriptive research method and associative method, while the data collection technique is done by using primary data and secondary data. Primary data is collected through distributing questionnaires and interviews, while secondary data is collected through literature study. The population in this study amounted to 42 people and used census techniques. In this study, quantitative analysis was performed using multiple regression analysis. The results of this statistical test study indicate that the variable has a significant effect between compensation on the performance of employees of Outsourcing PT. Indonesia Power UPJP Kamojang Bandung Regency and variable there is a significant influence between competence on employee performance Outsourcing PT. Indonesia Power UPJP Kamojang, Bandung Regency. By looking at the significant influence between compensation on employee performance Outsourcing PT. Indonesia Power UPJP Kamojang Bandung Regency and there is a significant influence between competence on employee performance Outsourcing PT. Indonesia Power UPJP Kamojang, Bandung Regency, the company must maintain the compensation given to employees in order to motivate work morale in achieving optimal work performance and employee competence must be maintained in order to achieve better company targets.